Label-Free Protein Analysis by Pyro-Electrohydrodynamic Jet Printing of Gold Nanoparticles - Vespini, Veronica; Grilli, Simonetta; Ferraro, Pietro; Rega, Romina; Ottevaere, Heidi; Nie, Yunfeng; Musto, Pellegrino; Pannico, Marianna (Frontiers in Bioengineering and Biotechnology, 2022)
The pyro-electrohydrodynamic jet (p-jet) printing technology has been used for the fabrication of confined assemblies of gold nanoparticles with a round shape and a diameter ranging between 100 and 200 m. The SERS performance of the p-jet substrate was evaluated by using Rhodamine 6G (R6G) as reference. The results demonstrate that this kind of SERS substrate exhibits strong plasmonic effects and a significant reproducibility of the signal with a coefficient of variation below 15%. We tested the signal behavior also in case of the Bovine Serum Albumin (BSA) as a model analyte, to demonstrate the affinity with biomolecules. Strong SERS activity was measured also for BSA across the whole spot area. The spectral patterns collected in different locations of the sensing area were highly reproducible. This observation was substantiated by multivariate analysis of the imaging datasets and opens the route towards a potential application of this kind of SERS substrate in biosensing.